Preventive exercises designed to reduce ankle joint pain using various methods in hammer throwers Overweight Baghdad clubs for ages (20-22) years (Al-Muthanna Journal of Sport Education Sciences, 2026)
This research aimed to develop a preventative program, designed and accompanied by assistive devices, for overweight female hammer throwers in athletics. The study investigated the effect of these preventative exercises, with the aid of assistive devices, on reducing ankle pain. This was based on the strength of the ankle extensor and flexor muscles in these overweight hammer throwers. The researcher hypothesized that there would be statistically significant differences between the pre-test and post-test results, favoring the post-test results. The researcher employed a single-group experimental design with pre- and post-tests, deemed suitable for the nature of the research. The sample consisted of eight hammer throwers in athletics: two for the pilot study and six for the main study. These athletes, all suffering from ankle pain due to their excess weight, were selected purposively from among those complaining of ankle pain. The program included preventative exercises for agility, balance, and jumping muscle strength. The study focused on ankle joint extension and flexion exercises (24 units of preventative rehabilitation, three days a week: Saturday, Tuesday, and Thursday). After completing the preventative exercises, post-tests were conducted. One of the most important findings was that the preventative exercises developed by the researcher had a positive effect on improving and reducing ankle joint pain. These exercises, designed with the use of various assistive devices, also contributed to weight loss among overweight female hammer throwers aged 20-22 years. The researcher recommended the continued use of preventative exercises designed with assistive devices to accelerate the treatment process for injured athletes